Aktivitas Antifungi Isolat Actinomycetes dari Sumber Air Panas Ai Sipatn Lotup Sanggau Terhadap Isolat Hortaea werneckii (T1) - Novik Nurhidayat, Jerliman Manalu, Rahmawati (Jurnal Protobiont, 2019)
Pathogenic fungi cause health problems especially the skin infection caused by Hortaea werneckii causes of tinea nigra skin disease. One of the method minimizes the problems and against the growth of Hortaea werneckii can use the active material from Actinomycetes bacteria as the antifungal. This research was to aware the kind of Actinomycetes bacteria that have the most potential as antifungal against the Hortaea werneckii, the effect of metabolic volume composition and incubation time of Actinomycetes bacteria against the Hortaea werneckii (T1). Antifungal activity test used the filtration method of Actinomycetes bacteria with parameters based on incubation time and volume comparison of metabolites concentration. Antifungal activity test of 11 isolates Actinomycetes bacteria produce six isolates Actinomycetes bacteria as the most potential antifungal and the percentage of the effect difference among the treatment against Hortaea werneckii (T1) are Thermoactinomyces sp. (H24) 39,98%, Thermoactinomyces sp. (H21) 29,11%, Thermobifida sp. (S311) 21,14%, Streptomyces sp. (S211) 34,21%, Actinomadura sp. (S21(2)) 24,70%, dan Nocardiopsis sp. (H22*1) 33,03%. Bacteria isolate Thermoactinomyces sp. (H24) have a significant percentage of antifungal with an average 97%, as a difference of the effect among treatments are 39,98%. The metabolites produced by Actinomycetes cause Hortaea werneckii (T1) growth to be inhibited and damage cells structure their.